Hubungan antara Kompetensi Sosial Guru dan Minat Belajar Siswa Kelas X (Sepuluh) pada Mata Pelajaran Sejarah Kebudayaan Islam (SKI) di MAN 2 Kota Bogor” - Ratu Balqis Sholiha; Sri Nurul Milla; Hilman Hakiem (EduInovasi: Journal of Basic Educational Studies, 2023)
The background of the problem in this study, namely the low interest in learning of class X (Ten) students in learning Islamic cultural history (SKI) at MAN 2 Bogor City, this research aims to find out whether there is a "relationship between teacher social competence and interest in students of class X (Ten) in the subject of Islamic cultural history (SKI) at MAN 2 Bogor City. The research used by researchers is quantitative research and correlation methods. The data source that the researcher obtained was the result of the questionnaire answers which the researcher distributed to 200 "respondents". The results of this study indicate that there is a positive and significant relationship between the two variables with a correlation coefficient value (R = 0.48, Sig (2-tailed) = 0.003) and based on the value of the coefficient of determination shows a number of 68.61%, which means the level value the social competence of the SKI teacher is included in the good category, while 70.76% means the level of interest in learning of class X (Ten) students in SKI subjects at MAN 2 Bogor City. The conclusion from this study is that the higher the social competence of the teacher, the higher the learning interest of class X (Ten) students in SKI subjects at MAN 2 Bogor City. Keywords: Social Competence; Learning Interest; History of Islamic Culture